Differentiated English Learning Assessment Viewed from Student Learning Styles - Jaya Putra, I Gede Ardika; Ni Wayan Surya Mahayanti; G A P Suprianti (Universitas Pendidikan Ganesha, 2023)
The problem with this research is that teachers do not understand the concept of differentiated learning and assessment tailored to student's learning styles and have not appropriately identified variations in students' learning styles. This hinders the implementation of diverse learning strategies that suit students' needs. This study aims to evaluate and determine the needs of teachers and students in developing learning style-based differentiation assessment instruments. This type of research is descriptive qualitative with a case study design. The research subjects were three teachers and 17 students as pilot test subjects. Data collection was conducted through in-depth interviews with teachers and distributing questionnaires to students. The instruments used were interview guides and learning-style questionnaires. Data analysis was performed using qualitative thematic analysis techniques. The results showed that teachers did not understand the concept of differentiated assessment and had not identified students' learning styles effectively. Based on the questionnaire, grade 6 students show significant variations in learning styles. In conclusion, differentiated assessment is urgent to meet the diversity of student learning styles. This research implies the need for teacher training in designing and implementing differentiated assessments based on student's learning styles to support more effective learning.